Ascertaining The Factors Determining Brain Drain Among Final Year Medical Students And House Officers In Tertiary Institutions In South-South Nigeria (Eurasian Medical Research Periodical, 2025)
Brain drain (BD) is the movement of healthcare professionals from a country of poor standard of living to a country with high or better of living. In Nigeria, brain drain among healthcare professionals is on the increase and this is affecting the healthcare sector by creating a vacuum or caused shortage of manpower in the sector. Barin drain is an important issue that the government must give attention to the determining factors in order to curtail future occurrence. The aim of this study is Ascertaining Factors Determining Brain Drain Among Final Year Medical Students and House Officer in Tertiary Institutions in South-South Nigeria. This was a cross-sectional study involving 350 (final year medical students 200 and house officers 150). A well-structured questionnaire was administered to participants. The study lasted for a period of 2 months. Exclusion criteria were those medical students who were not in final year and doctors that were not house officers. Inclusion criteria were final medical students and house officers. This study used a simple random sample of 200 participants, calculated using the Taro Yamane formula, and data were analyzed with SPSS version 25.0. The results of the study shows that 57.1% were final year students while 42.9% were medical officers The study revealed that 71.4% of the House Officers do not enjoy their profession and 85.7% are planning to leave the country, 71.4% said working environment favourable, 80.0% have bad working relationship with your consultants, 85.7% said no automatic job and 71.4% find difficult in passing primaries. The research shows that 85.7% of the final medical students faced tough academic environment.